Effectiveness of the IMFeD tool for the Identification and Management of Feeding Difficulties in Taiwanese children - Chieh-Chung Lin; Yen-Hsuan Ni; Lung-Huang Lin; Beng-Huat Lau; Hsun-Chin Chao; Hung-Chang Lee (Pediatrics and Neonatology)
Background: The Identification and Management of Feeding Difficulties (IMFeD™) tool was introduced in 2011 for management of children with feeding difficulties and has been used in various countries around the world. This study aimed to assess its acceptance and effectiveness in clinical practice in Taiwan. Methods: This was a prospective, observational, multicenter study where subjects were followed over 3 months. Outpatients identified as picky eaters, having poor appetite, poor weight gain, or weight loss were enrolled. The acceptance and effectiveness of IMFeD tool were evaluated by caregivers and pediatricians. Results: Among 423 children who completed the study (235 boys, 188 girls; 78.8% aged <5 years, 21.3% aged 6–10 years), the most common feeding difficulties were poor appetite in a fundamentally vigorous child (85.3%) and highly selective intake (70.2%). Mean percentiles for height and weight were 34.6 ± 25.3 and 20.3 ± 21.3 at enrolment, and increased by 5.4 and 5.9 (p < 0.0001) at the last visit, respectively. Most caregivers (86.5%) thought that the IMFeD tool helped them to understand and better identify picky eating behaviors. Pediatricians reported that the IMFeD tool was effective in 99.3% of patients for managing picky eaters in clinical practice. Conclusions: The IMFeD tool was effective in addressing differences in needs according to type of feeding difficulty by providing a systematic approach to manage feeding difficulty in Taiwanese children. It is applicable to the clinical practice and well-accepted by pediatricians and caregivers. Key Words: children, feeding difficulties, IMFeD tool